2010
DOI: 10.1089/env.2010.0001
|View full text |Cite
|
Sign up to set email alerts
|

Learning Outcomes among Students in Relation to West Virginia Coal Mining: an Environmental Riskscape Approach

Abstract: Children who live in coal mining areas are subject to environmental and socioeconomic risks for poor cognitive developmental outcomes. To assess the potential impact of the coal mining environmental riskscape on cognitive development in West Virginian children, we examined the associations between coal mining and learning outcomes among students in West Virginia public schools for the years 2005-2008. The study used a retrospective, natural field experiment design to test pass rates on standardized school perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…One study documented that school children in West Virginia mining areas show evidence of poorer cognitive development as measured by higher failure rates on standardized tests, controlling for other risk variables (Cain and Hendryx, 2010). A second paper showed that pregnant mothers who lived in mining counties in West Virginia were at higher risk for a low birth weight delivery, controlling for other risks (Ahern et al, 2011b).…”
Section: Epidemiological Evidence Of Public Health Disparities In Appmentioning
confidence: 99%
“…One study documented that school children in West Virginia mining areas show evidence of poorer cognitive development as measured by higher failure rates on standardized tests, controlling for other risk variables (Cain and Hendryx, 2010). A second paper showed that pregnant mothers who lived in mining counties in West Virginia were at higher risk for a low birth weight delivery, controlling for other risks (Ahern et al, 2011b).…”
Section: Epidemiological Evidence Of Public Health Disparities In Appmentioning
confidence: 99%
“…Indeed, studies of the riskscape have developed their own logics to demonstrate how risk is relational as mediated by sociomaterialistic arrangements. For instance, riskscape scholarship has concentrated on the interface between social and environmental concerns, exploring, for example, environmental justice (Cain & Hendryx, 2010; Lee et al, 2018) or health disparities, and their intersection with environmental hazards (Jenerette et al, 2011; Morello‐Frosch et al, 2001). Although urban spaces and phenomena such as gentrification (Abel & White, 2015) have featured within riskscape scholarship, discussions of home and TEC specifically have not yet been explored.…”
Section: Home‐ing In On Risk and Tec: A Literature Reviewmentioning
confidence: 99%
“…Studies show that students' learning achievements are associated with family, school, and community factors (Wokadala, 2016;Coulidiati-Kielem, 2016). Family factors often shown as related to students' learning achievements are socioeconomic status (SES), parental education, and having textbooks at home (Cain & Hendryx, 2010;Sikora et al, 2019;Thomson, 2018;Dudaitė, 2016). Literature usually conceptualizes them as family status factors (e.g., income, parental education, social class) and family process factors (e.g., parental involvement, disciplinary factors, parenting) (Bowen et al, 2012;Gubbins & Otero, 2016).…”
Section: Potential Factors Explaining Learning Inequalities Between Gma and Ngmamentioning
confidence: 99%